Organisational knowledge, professional practice and the professional doctorate at work - Lee, Alison; Green, Bill; Brennan, Marie (Research and Knowledge at Work, 2000)
The relationship between what might be termed 'organisational knowledge' and higher education has always been complex, dynamic and contested. The university, primary institution for the formal accreditation of knowledge and higher learning during most of this century, has at the same time faced extensive critique for its consistent privileging of disciplinary and formal modes of knowledge production over the more situated knowledges and practices of knowledge production within workplaces (a canonical text in this regard being Schön 1983). In recent times, the rapid development of what has been termed the 'knowledge society' (Gibbons et al 1994; Stehr 1994) has placed new demands on higher education. The university has come under pressure from a number of angles with regard to its role in the production of the new populations of 'knowledge workers' required by the 'new work order' of late capitalism (Gee et al 1996). In the 1980s, education increasingly became linked to economic development in the context of globalised capitalism. Higher education, in particular, has been under major redefinition in its relation to the economy and work. Indeed, as Scott (1997:36) notes, this relationship, while 'always latently dominant, ...is now seen as the key determinant of the university's future development'. As funding pressures impact upon universities, they have responded by attempting to turn themselves into quasi-businesses. Such developments have had important effects on their external relationships, as well as their internal dynamics.